The Ifluence Of Audit Fee, Auditor Reputation, Audit Opinion and Management Changes On Auditor Switching - Annisa Sartika, Husnul; Rahma Sari, Intan (Jurnal Penelitian Ekonomi Dan Akuntansi, 2024)
This research aims to determine and obtain empirical evidence of the influence of audit fees, auditor reputation, audit opinion, and management changes on auditor turnover. This type of research is quantitative research and uses secondary data in the form of audited annual financial reports sourced from the official website of the Indonesia Stock Exchange (BEI). The population in this research is transportation sector companies registered on the BEI during 2018-2022, with 37 companies as the population, and the sample technique used was purposive sampling, meeting the criteria of 10 companies sampled in 5 years of observation. The data analysis technique in this research uses logistic regression analysis in the Eviews 9 software application. The results of this research show simultaneously that audit fees, audit reputation, audit opinion, and management changes affect auditor changes. And partially shows that audit fees, audit reputation, audit opinion, and management changes have an influence on auditor changes.